Karakteristik Fisikokimia Tepung Singkong dengan Beberapa Metode Modifikasi - Bella Dwi Pasca; Tjahja Muhandri; Dase Hunaefi; Budi Nurtama (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
The limited use of cassava for industrial purposes encourages the development of various derivative products from cassava including cassava flour. However, cassava flour has unfavorable characteristics when used directly as raw material for food products so it must be modified. The aims of this study were to modify cassava flour, and to identify characteristic from several modified cassava flour. The cassava variety used was cimanggu. This study used completely randomized design (CRD) with three treatments of modification, each in triplicate. The modification methods used were spontaneous fermentation of cassava flour suspension for 36 hours (TSFS), fermentation of sliced cassava for 48 hours (TG), and heat moisture treatment of cassava flour at moisture content of 20% with temperature of 121oC for 15 minutes (TS HMT). The modified cassava flour was dried, then analyzed for amylose content, whiteness index, and pasting properties. The results showed that TSFS modification increased amylose content and pasting temperature, but it decreased the breakdown viscosity. TG modification increased the amylose content, whiteness index, viscosity (peak, final, setback), and pasting temperature, but it decreased breakdown viscosity. TS HMT modification increased pasting temperature, but it decreased viscosity (peak, breakdown, final, setback) and whiteness index.